Career Adaptability : Studi Deskriptif Pada Karyawan Gen Z - Farah Fauziyah Fitri; Rima Mudhiah Putri Aiman; Christie Naomi Rotua Angelica; Nadhira Tita Azaria Putri; Kiky Dwi Hapsari Saraswati (Jurnal Ilmiah Psyche, 2023)
Generation Z are individuals born between 1995 and 2012, so they are in a transition between the academic world and the world of work. The difference between the two situations certainly requires good adaptability so as not to have a negative impact on their psychological well-being. This study aims to get an overview of career adaptability in Generation Z employees. Career adaptability is individual readiness to cope with job changes and work situations in a corporate environment. This research is a quantitative study by asking 64 participants to fill out 24 items of the Career Adaptability Scale (CAAS) questionnaire developed by Savickas and Porfeli (2012). Based on the results of data analysis, men (M=4.271, SD=0.528) have slightly higher career adaptability than women (M=4.250, SD=0.443). Ages 20-21 years (M=4.413, SD=0.395) had the highest and lowest career adaptability at ages 22-23 years (M=4.164, SD=0.499). Gen Z who work for 1-2 years (M=4.358, SD=0.466) have high career adaptability compared to those under 6 months (M=4.25, SD=0.444) and 6 months-1 year (M=4.160, SD=0.466).